Punishment and crime: the limits of punitive crime control - Kleck, Gary (Routledge, 2018)
Acknowledgements -- Introduction -- Theory : the mechanisms by which legal punishment might reduce crime -- Deterrence and the rational choice model of criminal behavior : the case of the disappearing theory -- General methodological problems in punishment research -- Individual-level research on general deterrence : the impact of perceptions of legal risk on criminal behavior -- Individual-level research on the effects of punishment on the punished : special deterrence -- Macro-level research on the effect of punishment levels -- The impact of capital punishment on murder rates -- The missing link between macro-level and individual-level effects : the impact of macro-level punishment levels on individual perceptions of legal risk -- Incapacitative effects of incarceration and the impact of imprisonment rates -- Crime-increasing effects of punishment -- Conclusions -- Index